Ukrainian Antarctic Research: Current Bibliography (July 2007-June 2009) - Rybachuk, V. P.; Videnina, N. G. (Ukrainian Antarctic Journal, 2009)
The bibliographic descriptions of the Ukrainian scientific works on Antarctica that were published domestically and abroad in 2008 and 2009 as well as additional materials issued in 2007 are listed herein. This bibliographic data extends and complements the 1997–2007 bibliography of national publications, presented in the scientific issue "Ukrainian Antarctic Research" (V.P. Rybachuk, P.F. Gozhik, N.G. Videnina, and V.A. Litvinov, Ed. P.F. Gozhik, 2008, Kiev, Varta Publishers, 286 p., ISBN 978-966-02-4803-8). The abstracts were collected from Ukrainian scientific journals, collections, and conference proceedings as well as national (“Dzherelo”, “Litopys zhurnal’nykh statej”, etc.) and international (“Antarctic Bibliography”, Scopus, Google scholar, Scirus) bibliographic databases. In total 121 publications were compiled on the topics of Antarctic research within the last two years. The references were arranged under the subject headings based on those used by the "Ukrainian Antarctic Research" issue.